PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII8 SMP NEGERI 14 PEKANBARU - Trisna Wenti; Sakur Sakur; Elfis Suanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was based on the students’ achievement in learning mathematics especially grade VIII8 of SMPN 14 Pekanbaru under the Mastery Minimum Criteria with percentage of 38,23%. The subject of basic competence were about triangle. The teacher-centered learning was still used to teach materials during the learning process. The research conducted was the Classroom Action Research. The aims of this research is to improve the learning process and results on the students learning mathematic by implementing cooperative learning model structural approach of Think Pair Share (TPS). There were 34 students in the class consisting 17 boys and 17 girls as the participant of this research. The instruments of data collection in this research were observation sheets to observe the activities of teacher and students and students Mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students’ Mathematic tests were analyzed in quantitative desciptive. The qualitative desciptive showed an improvement of learning process prior to the action on the first and second cycles. The results of this research showed an increasing number of students learning Mathematic from the basic score with percentage 38,23% to 61,76% on the first test and 79,41% on second test. Based on the result of this research could be concluded that the implementation of Cooperative Learning Model structural approach of Think Pair Share (TPS) can improve the students’ achievement of learning Mathematic in grade VIII8 of SMPN 14 Pekanbaru in the first semester academic years 2018/2019.Key Word: Students’ Math Achievement, Cooperative Learning Model Structural Approach of Think Pair Share (TPS), Clasroom Action Research